Perbandingan Hasil Belajar Siswa Melalui Strategi Pembelajaran Joyful Learning dan Everyone Is A Teacher Here Kelas X Teknik Sepeda Motor (TSM) Dan Kelas X Teknik Gambar Bangunan (TGB) Pada Materi Termodinamika - Dewi, Sulasteri; Rafiqah, Rafiqah; Suhardiman, Suhardiman (Al-Khazini, 2021)
The purpose of this study is to: compare learning outcomes between students who are taught the Joyful Learning strategy with the Every One is A Teacher Here strategy on thermodynamics class X SMKN 1 South Sulawesi. This type of research is classified as pre-experimental using a comparative study research approach, learning outcomes after being taught using the Joyful Learning learning strategy with the Every One is A Teacher Here learning strategy for students in class X TSM and class X TGB. The results showed that the class taught using the Joyful Learning learning strategy the average value of the students was in the good predicate category (B+), and the class taught using the Every One is A Teacher Here learning strategy the average student score was in the good category (B). It was concluded that there was a difference between the classes taught using the Joyful Learning learning strategy with higher learning outcomes than the classes taught using the Every One is A Teacher Here learning strategy.The implications of this research are: In learning physics to get high participation from each student, as an option, you can use the Every One Is a Teacher Here learning strategy, and to make students not feel pressured, they can use the Joyful Learning learningstrategy as an option.